Key beliefs of hospital nurses' hand‐hygiene behaviour: protecting your peers and needing effective reminders. (7th April 2015) - White, Katherine M.; Jimmieson, Nerina L.; Graves, Nicholas; Barnett, Adrian; Cockshaw, Wendell; Gee, Phillip; Page, Katie; Campbell, Megan; Martin, Elizabeth; Brain, David; Paterson, David
Abstract : Issues addressed: Hand hygiene in hospitals is vital to limit the spread of infections. This study aimed to identify key beliefs underlying hospital nurses' hand‐hygiene decisions to consolidate strategies that encourage compliance. Methods: Informed by a theory of planned behaviour belief framework, nurses from 50 Australian hospitals (n = 797) responded to how likely behavioural beliefs (advantages and disadvantages), normative beliefs (important referents) and control beliefs (barriers) impacted on their hand‐hygiene decisions following the introduction of a national '5 moments for hand hygiene' initiative. Two weeks after completing the survey, they reported their hand‐hygiene adherence. Stepwise regression analyses identified key beliefs that determined nurses' hand‐hygiene behaviour. Results: Reducing the chance of infection for co‐workers influenced nurses' hygiene behaviour, with lack of time and forgetfulness identified as barriers. Conclusions: Future efforts to improve hand hygiene should highlight the potential impact on colleagues and consider strategies to combat time constraints, as well as implementing workplace reminders to prompt greater hand‐hygiene compliance. So what?: Rather than emphasising the health of self and patients in efforts to encourage hand‐hygiene practices, a focus on peer protection should be adopted and more effective workplace reminders should be implemented to combat forgetting.